Analysis of amplang business in Babulu Laut Village, Babulu District, North Penajam Paser Regency - Qur'ain, Siti Paturahmah; Haqiqiansyah , Gusti; Oktawati, Nurul Ovia (Faculty of Fisheries and Marine Science, Mulawarman University, 2024)
Amplang processing in Babulu Laut Village uses milkfish basic ingredients. This study aims at the amount of costs incurred during the production process, receipts and income from the amplang business in Babulu Laut Village, by sampling using the census method, where the population is amplang processors in Babulu Laut Village. Amplang business in Babulu Laut Village, Babulu District Incurred investment costs of Rp. 9,483,000 with depreciation of Rp. 125,051 / month, irregular costs during production of Rp. 931,280 and in a month amounted to Rp. 6,204,490, so as to obtain total costs incurred of Rp. 6,329,541/month. Revenue is Rp. 86,950,000 month with an average of Rp. 12,421,429/month. income of Rp. 42,643,216/month with an average of Rp. 6,091,888/month.